The validity and sensitivity of PANSS‐6 in treatment‐resistant schizophrenia. (30th August 2018) - Østergaard, S. D.; Foldager, L.; Mors, O.; Bech, P.; Correll, C. U.
Abstract : Objective: To test the validity and sensitivity of the six‐item version (PANSS‐6) of the 30‐item Positive and Negative Syndrome Scale (PANSS‐30) in treatment‐resistant schizophrenia (TRS). Method: Using data from the clozapine phase (2E) of the Clinical Antipsychotic Trials of Intervention Effectiveness (CATIE) study, we investigated the following: (i) The scalability of PANSS‐6 and PANSS‐30; (ii) The correlation between PANSS‐6 and PANSS‐30 total scores; (iii) Whether PANSS‐6 could identify cross‐sectional symptom remission; and (iv) The efficacy of clozapine, olanzapine, risperidone and quetiapine in TRS using the 'speed of change' on PANSS‐6 and PANSS‐30 (change in total score per week) as outcome measures. Results: We found that (i) only PANSS‐6 and not PANSS‐30 was scalable; (ii) The correlation between PANSS‐6 and PANSS‐30 total scores was high (Spearman coefficient: 0.85), (iii) PANSS‐6 accurately identified cross‐sectional symptom remission as defined by the Andreasen et al. criteria; and (iv) The only antipsychotic that caused improvement (speed of change significantly lower than 0 during the first three months of treatment) was clozapine, both when using PANSS‐6 (speed of change: −0.50 points/week; 95%CI: −0.84, −0.17) and PANSS‐30 (speed of change: −1.41 points/week; 95%CI: −2.80, −0.02) as outcome measures. Conclusion: PANSS‐6 validly measures severity, remission and antipsychotic efficacy in TRS.